PEMBERDAYAAN REMAJA PUTRI MELALUI PSIKOEDUKASI CINDERELLA COMPLEX DALAM MENINGKATKAN KEMANDIRIAN PSIKOLOGIS UNTUK MENCEGAH RASA KETERGANTUNGAN - Vivin Ainun Nuha; Ni’matuzahroh; Djudiyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Cinderella Complex is a psychological tendency in women characterized by a strong desire to be cared for and protected by others, particularly men, leading to emotional and psychological dependency. This condition requires early attention, especially among adolescent girls who are in the critical stage of identity formation and developing personal independence. This community service program aims to foster psychological independence and prevent dependency tendencies among adolescent girls through a Cinderella Complex psychoeducation program. The program was conducted with 25 female junior high school students selected through purposive sampling. The psychoeducation was delivered using a group empowerment method encompassing material presentation, interactive discussion, and self-reflection activities. Program effectiveness was measured using pre-test and post-test instruments, with data analyzed through the Wilcoxon Signed Rank Test. The results revealed a Z value of -4.378 with Asymp. Sig. (2-tailed) = 0.000 (p < 0.001), indicating a significant improvement in participants' knowledge and awareness following the program. All participants (100%) demonstrated score improvements after the intervention. Therefore, the Cinderella Complex psychoeducation program proved effective as a community empowerment initiative in raising awareness of the importance of psychological independence and preventing dependency tendencies from an early age. ABSTRAK Cinderella Complex merupakan kecenderungan perempuan untuk bergantung secara psikis, yang ditandai dengan keinginan kuat untuk dirawat dan dilindungi orang lain, terutama laki-laki. Kondisi ini perlu mendapat perhatian sejak dini, khususnya pada remaja perempuan yang berada pada masa pembentukan identitas dan kemandirian diri. Kegiatan pengabdian masyarakat ini bertujuan untuk membangun kemandirian psikologis dan mencegah ketergantungan pada remaja perempuan melalui program psikoedukasi Cinderella Complex. Kegiatan ini dilaksanakan terhadap 25 remaja putri tingkat SMP yang dipilih melalui teknik purposive sampling. Program psikoedukasi dilakukan dengan metode pemberdayaan kelompok yang mencakup pemberian materi, diskusi interaktif, dan refleksi diri. Efektivitas kegiatan diukur menggunakan nilai Z = -4,378 dengan Asymp. Sig. (2-tailed) = 0,000 (p < 0,001), yang mengindikasikan adanya peningkatan yang signifikan pada pengetahuan dan kesadaran peserta setelah mengikuti kegiatan. Seluruh peserta menunjukkan peningkatan skor setelah kegiatan berlangsung. Dengan demikian, program psikoedukasi Cinderella Complex terbukti efektif sebagai upaya pemberdayaan remaja putri dalam meningkatkan kesadaran akan pentingnya kemandirian dan pencegahan ketergantungan psikologis sejak usia remaja.